PENGELOLAAN ASET TONGKONAN DALAM KONTEKS GEREJA LOKAL: PERSPEKTIF MANAJEMEN GEREJAWI DI MASYARAKAT TORAJA - Astrid Dea Patadungan; Rini Reang Para’ra, Selciana Sriwahyuni Kidang, Rut Rande Bilik, Seprianti Sangga (ADISAM PUBLISHER, 2025)
Managing Tongkonan assets is the same as maintaining valuable assets in society, namely unity and togetherness. The aim of the research is to develop how families should manage assets from Tongkonan based on a management perspective in the church. Apart from that, it also aims to contribute to models that can be implemented by the church and society regarding building harmony within the church and Tongkonan. Several theories used by the author include the theory of tongkonan, the theory of church management, and the theory of society which have been developed and researched by previous authors. The research method in this paper uses a qualitative method with a descriptive approach. The qualitative method uses literature study sourced from books, articles and relevant internet sources. The results of this research are that the church provides an example for tongkonan in managing assets which are a form of inheritance in building unity, togetherness and harmony. This can be done by means of socialization by the church about good and correct management, it can also be done by preaching the gospel and interpreting the value of harmony in the Tongkonan house as a shared home